EFEKTIVITAS PENGELOLAAN DANA BANTUAN OPERASIONAL SEKOLAH DALAM MENINGKATKAN SARANA DAN PRSARANA PENDIDIKAN SMP SWASTA HKBP SIBOLGA - Vitra Linda Mawaty Pasaribu; Yacub Hutabarat; Tiurlina Hasmawati Sihite (CV. ALIM'SPUBLISHING, 2023)
This study aims to find out the opinions of teachers and administrative staff regarding the management of BOS funds at the HKBP Sibolga Private Middle School in terms of the procedures for managing, using, and targeting BOS funds. This research is quantitative descriptive. The subjects of this study were all teachers and administration staff of the HKBP Sibolga Private Middle School for the 2020/2021 academic year, a total of 20 people. Data collection techniques used questionnaires and documentation to obtain data regarding the management of BOS funds related to the procedures for managing, using, and targeting BOS funds. The analysis technique uses cross tabulation and crosstab methods. The results showed that 90% of respondents (18 teachers and 2 administrative staff) stated that the procedures for managing BOS funds at HKBP Private Middle Schools complied with the 2021 BOS technical guidelines and only 10% of respondents (1 teacher and 2 administrators) stated it is not in accordance with. Regarding the use of BOS funds at HKBP Sibolga Private Middle School, 88.5% of teacher respondents (15 people and 1 uhsah administrative staff) stated that it was appropriate and only 11.5% (1 teacher) stated that it was not on target. So, it can be concluded that the majority of respondents are of the opinion that the management of BOS funds at the HKBP Sibolga Private Middle School for the 2021/2022 school year from the procedures for managing, using, and targeting BOS funds is in accordance with the technical guidelines for using BOS funds in 2022